2019
DOI: 10.1186/s40635-019-0256-z
|View full text |Cite
|
Sign up to set email alerts
|

Early herpes and TTV DNAemia in septic shock patients: a pilot study

Abstract: Background Septic shock patients exhibit an increased incidence of viral reactivation. Precise timing of such reactivation—as an early marker of immune suppression, or as a consequence of the later—is not known precisely. Here, using a fully designed nucleic acid extraction automated procedure together with tailored commercial PCR kits, we focused on the description of early reactivation within the first week of ICU admission of several herpes viruses and Torque Teno virus (TTV) in 98 septic shock… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

8
24
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(34 citation statements)
references
References 32 publications
8
24
2
Order By: Relevance
“…Although we observed an increase in 28-day mortality in individuals with EBV reactivation compared to those without (24% vs 16%; p = 0.051), this was on the borderline of statistical significance. This is in keeping with three large studies focusing on sepsis patients 8,9,12 which used PCR to quantify EBV load. These studies did not find an association with EBV reactivation and mortality although one small study of critically ill sepsis and non-sepsis patients 19 did find a positive association.…”
Section: Discussionsupporting
confidence: 79%
See 3 more Smart Citations
“…Although we observed an increase in 28-day mortality in individuals with EBV reactivation compared to those without (24% vs 16%; p = 0.051), this was on the borderline of statistical significance. This is in keeping with three large studies focusing on sepsis patients 8,9,12 which used PCR to quantify EBV load. These studies did not find an association with EBV reactivation and mortality although one small study of critically ill sepsis and non-sepsis patients 19 did find a positive association.…”
Section: Discussionsupporting
confidence: 79%
“…Alongside this, studies describing a high frequency of viral reactivation in sepsis patients support the concept that previously immunocompetent individuals can develop a varying degree of functional immunosuppression in response to severe infection [8][9][10][11][12] . Walton and colleagues observed that 43% of septic patients had evidence of viraemia with multiple viruses 8 , the MARS consortium described a 68% frequency of herpesvirus viraemia amongst individuals with septic shock 9 , whilst Mallet and colleagues observed a 53% frequency of herpesvirus viraemia in individuals with septic shock 12 . In both studies, Epstein-Barr virus (EBV) was the most commonly observed reactivated virus at a frequency of 32-48% in plasma 8,9,12 .…”
mentioning
confidence: 80%
See 2 more Smart Citations
“…In this retrospective study covering a 5-year period, we found that HSV/ CMV reactivation was frequent and concerned more than half non-immunocompromised patients, which is higher than that described in previous studies including all ICU patients [4,8,14]. This might be explained by several reasons: the use of PCR to diagnose reactivation with a higher sensitivity than older technics, the age of our cohort of patients (with a high probability of seropositivity for HSV and CMV at ICU admission) and the frequency of sepsis with a probable induced "immunoparalysis" [24]. In our cohort, HSV reactivation occurred earlier than CMV reactivation and the median time of reactivation for both viruses was comparable to what is described in "non-ECMO" patients [25].…”
Section: Discussioncontrasting
confidence: 54%